Integrity in Public Life: Reflections on a Duty of Candour. (4th March 2022) - Gardiner, Simon; Morrison, Douglas; Robinson, Simon
Abstract : This article will evaluate whether a "duty of candour" on public employees including specifically health practitioners and police officers is an effective mechanism in terms for improving trust and openness. This is the context of the actions of the police in relation to the Hillsborough Stadium disaster in 1989 where 96 soccer fans died at the match due to ineffective policing. The formal identification of responsibility on the part of the police despite the attempt by the police to attribute blame elsewhere, was the starting point of a proposal for an explicit duty on officials in public bodies such as the police to tell the truth and be under a statutory "duty of candour." The article provides an overview of the duty of candour, its subsequent development, legislatively and professionally in the context of the British health care system, where it currently exists, and the potential impact for the police. It is argued that engagement with the paradox between professional and organizational duty expressed through the language of culture and truth telling is necessary to reassert the importance of trust and integrity in a range of public bodies.